2015
DOI: 10.17216/limnofish-5000083989
|View full text |Cite
|
Sign up to set email alerts
|

Manyas Gölü’ndeki (Balıkesir/Türkiye) Sazan Balığı için (Cyprinus carpio L., 1758) Fanyalı Uzatma Ağı Seçiciliği

Abstract: The aim of this study was determine the selectivity properties of trammel net which have 100, 110, 120, 130 and 140 mm mesh size for Cyprinus carpio in Manyas Lake. Fieldwork was carried out in two different stations of Manyas Lake, in a monthly period from April 2007 to March 2008 and with a total of 24 catching trials. The SELECT method was used to determine the selectivity parameters. In the experiments, 208 C. carpio with length ranges between 28.4-65.4 cm were caught. According to the Lognormal model, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…When comparison with previously studies conducted on gillnet for common carp (Table 6), similar optimum length were found by Balık (1999) with 13 cm mesh size (39.33 cm) and Yalçın (2006) with 10 (30.4 cm) and 12 cm (36.5 cm) mesh sizes. However, Cilbiz et al (2015) presented model lengths of 10, 12 and 14 cm mesh size of trammel nets as 39.05 cm, 46.85 cm and 54.66 cm from Lake Manyas, respectively. In addition, model lengths reported by Carol and García-Berthou (2007) for 10.15 cm mesh size of gillnets (38.12 cm) very higher then ours 10 cm mesh size result (31.00 cm).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When comparison with previously studies conducted on gillnet for common carp (Table 6), similar optimum length were found by Balık (1999) with 13 cm mesh size (39.33 cm) and Yalçın (2006) with 10 (30.4 cm) and 12 cm (36.5 cm) mesh sizes. However, Cilbiz et al (2015) presented model lengths of 10, 12 and 14 cm mesh size of trammel nets as 39.05 cm, 46.85 cm and 54.66 cm from Lake Manyas, respectively. In addition, model lengths reported by Carol and García-Berthou (2007) for 10.15 cm mesh size of gillnets (38.12 cm) very higher then ours 10 cm mesh size result (31.00 cm).…”
Section: Discussionmentioning
confidence: 99%
“…Common carp (Cyprinus carpio L., 1758) is one of the main target species in Turkey Inland fisheries. This species distributes through Turkey (Cilbiz et al, 2015) and landings reached 13718 t in 2005 and then decreased to 8036 t in 2014 (TUIK, 2015). This might be due to; overfishing, pollution, diseases and parasites habitat degradation and invasive species (such as Carassius gibelio reported by Emiroğlu (2011)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation